2016
DOI: 10.1253/circj.cj-15-1269
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Compacted Myocardial Abnormalities by Cardiac Magnetic Resonance With Native T1 Mapping in Left Ventricular Non-Compaction Patients – A Comparison With Late Gadolinium Enhancement –

Abstract: Background: Native T1 mapping is an emerging cardiac magnetic resonance technique for quantitative evaluation of cardiomyopathies. This study aimed to investigate the usefulness of native T1 mapping in characterizing myocardial abnormalities in left ventricular non-compaction (LVNC) by comparing it with late gadolinium enhancement (LGE). Methods and Results:The study group of 31 LVNC patients and 8 normal controls underwent cardiovascular magnetic resonance to acquire the native T1 maps and LGE images. Of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
(23 reference statements)
3
17
0
5
Order By: Relevance
“…31 Despite these limitations, the need to study and develop new and more accurate imaging techniques is underscored by recent human studies suggesting that the commonly used definition of LVNC as a trabeculated to compact myocardium ratio >2.3 needs to be reconsidered. [40][41][42] Overall, the data and methodology presented in this study represent the proof-of-principle that the mouse ventricular wall can be structurally resolved and evaluated in 3D with micro-CT, providing a valid addition to the traditional 2D histological assessment of compact myocardial thickness in mouse embryos. Although the present study was performed on iodine-stained fixed specimens, it demonstrates what is methodologically achievable, including spatial resolution, using current imaging and image analysis techniques.…”
Section: Discussionmentioning
confidence: 98%
“…31 Despite these limitations, the need to study and develop new and more accurate imaging techniques is underscored by recent human studies suggesting that the commonly used definition of LVNC as a trabeculated to compact myocardium ratio >2.3 needs to be reconsidered. [40][41][42] Overall, the data and methodology presented in this study represent the proof-of-principle that the mouse ventricular wall can be structurally resolved and evaluated in 3D with micro-CT, providing a valid addition to the traditional 2D histological assessment of compact myocardial thickness in mouse embryos. Although the present study was performed on iodine-stained fixed specimens, it demonstrates what is methodologically achievable, including spatial resolution, using current imaging and image analysis techniques.…”
Section: Discussionmentioning
confidence: 98%
“…Besides these reports of focal fibrosis or scars in patients with LVNC, Jenni et al (26) revealed interstitial fibrosis as a finding in six of seven hearts with a diagnosis of LVNC. Zhou et al (27) recently reported subjects with a diagnosis of LVNC had a significantly longer native T1 time measure in the clinic, it is not specific (33.2% [247 of 745] of subjects in the MESA cohort with NCC . 2.3).…”
Section: Relationship Between LV Trabeculation and Measures Of Diffusmentioning
confidence: 99%
“…Table 1 in the paper indicates that the family history was significantly more often positive for LVHT in LGE− LVHT patients as compared with LGE+ LVHT patients. 1 What is the explanation for LGE− LVHT patients more frequently having a positive family history for LVHT than the LGE+ LVHT patients? The finding suggests that LGE− LVHT patients more frequently have a genetic background than LGE+ LVHT patients.…”
mentioning
confidence: 99%
“…Finally, group sizes should be increased to draw final conclusions. 1 We have the following comments and concerns. We do not agree with the statement that higher T1-values in LGE+ LVHT patients than in LGE− LVHT patients suggest that T1-mapping is more sensitive than LGE for demonstration of myocardial fibrosis.…”
mentioning
confidence: 99%